Gyroscope of the direction with structural redundancy - Карачун, Владимир Владимирович; Мельник, Виктория Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The effectiveness of the scheme with structural redundancy for umensheniya drift axis of the figure of a free gyroscope in a quasi-harmonic rocking base. Poster scaled-down test reveals the influence of the angular motion of the aircraft on the error kursoukazaniya